RGD-Human Serum Albumin Conjugates as Efficient Tumor Targeting Probes - Kai Chen; Jin Xie; Xiaoyuan Chen (Molecular Imaging)
Cyclic arginine-glycine-aspartate (RGD) peptides and their derivatives have been intensively studied as tumor targeting probes. One major drawback, however, is their short blood circulation half-lives, which greatly compromises their targeting efficacy. To address this issue, a cyclic peptide, c(RGDyK), and an organic dye (IRDye800 or Cy5.5) were covalently conjugated onto human serum albumin (HSA). The conjugates were subjected to in vitro cell staining, in vivo near-infrared fluorescence (NIRF) imaging, ex vivo NIRF imaging, and histologic studies to evaluate their feasibility as tumor imaging probes. As a control, RAD peptide was also coupled with HSA and labeled with IRDye800 for in vivo imaging. The HSA-RGD-IRDye800 exhibited integrin α v β 3 -specific binding in cell staining experiment. In vivo NIRF imaging showed higher tumor accumulation and tumor to background contrast of HSA-RGD-IRDye800 over RGD-IRDye800. The integrin specificity of HSA-RGD-IRDye800 is confirmed by both successful inhibition of tumor uptake in the presence of c(RGDyK) and the inability to accumulate in integrin-positive tumors by RAD-HSA-IRDye800. Histologic examination revealed initial tumor vascular binding and eventually both tumor vasculature and tumor cell integrin binding in vivo. In summary, we successfully developed an RGD-based protein conjugate with prolonged circulation half-life for NIRF imaging of tumor integrin α v β 3 expression. The success of this study may be generalizable for other peptide-based probes to be conjugated with HSA for prolonged tumor contrast and improved pharmacokinetics.